2020
DOI: 10.1016/s0140-6736(20)32236-4
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor versus clopidogrel in elective percutaneous coronary intervention (ALPHEUS): a randomised, open-label, phase 3b trial

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 30 publications
3
43
2
Order By: Relevance
“…Interestingly, among those patients with previous PCI, the effects on MACE and mortality were consistent irrespective of the time elapsed since the last PCI. Finally, the ALPHEUS trial found that ticagrelor was not superior to clopidogrel in reducing periprocedural myocardial necrosis in stable coronary patients undergoing high-risk elective PCI but caused an increase in minor bleeding at 30 days [107].…”
Section: Adjunctive Pharmacotherapy and High Bleeding Risk Patientsmentioning
confidence: 99%
“…Interestingly, among those patients with previous PCI, the effects on MACE and mortality were consistent irrespective of the time elapsed since the last PCI. Finally, the ALPHEUS trial found that ticagrelor was not superior to clopidogrel in reducing periprocedural myocardial necrosis in stable coronary patients undergoing high-risk elective PCI but caused an increase in minor bleeding at 30 days [107].…”
Section: Adjunctive Pharmacotherapy and High Bleeding Risk Patientsmentioning
confidence: 99%
“…While use of intensive P2Y12 inhibition is superior to clopidogrel in the setting of ACS [ 87 ], the benefits are less clear in elective PCI [ 88 ]. ALPHEUS (assessment of loading with the P2Y12 inhibitor ticagrelor or clopidogrel to halt ischaemic events in patients undergoing elective coronary stenting) [ 89 ] randomised 1883 patients undergoing elective PCI to ticagrelor vs. clopidogrel loading. Ticagrelor was not associated with any difference in the primary outcome (PCI-related type 4 MI or major myocardial injury at 48 h) (35% vs. 36%; OR 0.97, 95% CI 0.80 to 1.17; p = 0.75) or major bleeding, but was associated with increased minor bleeding (11% vs. 8%; OR 1.54, 95% CI 1.12 to 2.11; p = 0.0070) supporting clopidogrel remaining the standard of care in elective PCI.…”
Section: Methodsmentioning
confidence: 99%
“…Ticagrelor may not provide benefit in low-risk individuals undergoing elective PCI. With the aim to reduce prognostically-important periprocedural myonecrosis [135] [18]. A similar lack of effect on periprocedural myonecrosis was also observed in a small study of elective PCI patients comparing ticagrelor 90 mg or 60 mg BD with clopidogrel [50].…”
Section: Studies Of Ticagrelor In Percutaneous Coronary Interventionmentioning
confidence: 73%
“…Overall, the PEGASUS-TIMI 54 trial demonstrated that, for patients at high risk of recurrent ischaemic events, a longer duration of DAPT may derive benefit, but this needs to be weighed against the higher risk of non-fatal bleeding. In selecting those most likely to benefit from long-term DAPT, further subgroup analysis of PEGASUS-TIMI 54 supported Stroke or death at 30 days: 5.5% vs. 6.6%; HR, 0.83; 95% CI 0.71-0.96; P = 0.02 GUSTO severe bleeding at 30 days: 0.5% vs. 0.1%; HR, 3.99; 95% CI 1.74-9.14; P = 0.001 ALPHEUS (2020) [18] 1910 patients with stable CAD with an indication for PCI and at least 1 high-risk feature † Ticagrelor (180 mg LD, 90 mg BD MD) (87% on aspirin at admission) for 30 days Clopidogrel (300-600 mg LD, 75 mg OD MD) (85% on aspirin at admission) for 30 days PCI-related type 4 (a or b) MI or major myocardial injury at 48 h: 35% vs. 36%; OR, 0.97; 95% CI 0.80-1.17; P = 0.75 Major bleeding (BARC 3 or 5) at 48 h: <1% vs. 0%; P = 0.50 Minor bleeding (BARC 1 or 2) at 30 days: 11% vs. 8%; OR, 1.54; 95% CI 1.12-2.11; P = 0.007 * One of the following: ≥65 years old, diabetes treated with medication, a second prior spontaneous MI, multivessel CAD, chronic renal dysfunction (estimated creatinine clearance <60 mL per minute). † ≥75 years old, renal insufficiency (clearance <60 mL per minute), diabetes mellitus, overweight (BMI >30 kg/m 2 ), history of ACS in last year, left ventricular ejection fraction <40% and/or prior episode of heart failure, multivessel (2-3) disease, multiple stents or total stent length >30 mm, left main stenting, ACC/AHA type B2 or C lesion, stenting of venous or arterial coronary graft.…”
Section: Phase III Studies Of Ticagrelor In Coronary Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation